2017
DOI: 10.1073/pnas.1703151114
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer cell integrins using gold nanorods in photothermal therapy inhibits migration through affecting cytoskeletal proteins

Abstract: Metastasis is responsible for most cancer-related deaths, but the current clinical treatments are not effective. Recently, gold nanoparticles (AuNPs) were discovered to inhibit cancer cell migration and prevent metastasis. Rationally designed AuNPs could greatly benefit their antimigration property, but the molecular mechanisms need to be explored. Cytoskeletons are cell structural proteins that closely relate to migration, and surface receptor integrins play critical roles in controlling the organization of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 95 publications
(97 reference statements)
2
113
0
1
Order By: Relevance
“…Furthermore, the highest increase in calcium signal was observed, and calcium response was likely due to inflow of calcium as well as intracellular signaling via the inositol trisphosphate (IP3) pathway. Recently, El-Sayed et al (Ali et al, 2017) demonstrated that AuNPs with integrin-targeting properties could inhibit cancer cell migration through affecting cytoskeletal proteins. Arg-Gly-Asp (RGD) peptide-functionalized gold nanorods (AuNRs) were fabricated and further activated with 808-nm near-infrared (NIR) light to generate heat for photothermal therapy.…”
Section: Gold Nanoparticlementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the highest increase in calcium signal was observed, and calcium response was likely due to inflow of calcium as well as intracellular signaling via the inositol trisphosphate (IP3) pathway. Recently, El-Sayed et al (Ali et al, 2017) demonstrated that AuNPs with integrin-targeting properties could inhibit cancer cell migration through affecting cytoskeletal proteins. Arg-Gly-Asp (RGD) peptide-functionalized gold nanorods (AuNRs) were fabricated and further activated with 808-nm near-infrared (NIR) light to generate heat for photothermal therapy.…”
Section: Gold Nanoparticlementioning
confidence: 99%
“…For cell adhesion, the number of cells adhered on plates gradually increased with decreasing particle AR, and the expression of adhesion molecules in cells treated with MSNs decreased with increasing particle AR. For cytoskeleton, when A375 cells incubated with 0.1 mg/ml NS100 or NSR240, F-actin proteins Changes in the cell shape using DIC images before and after AuNR or NIR treatments (Ali et al, 2017). Reprinted with permission from Ali et al (2017).…”
Section: Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the treatment is still in the research phase, the team sees it being used for head, neck, breast and skin cancers with direct local injections. They also suspect they would be able to treat deeper cancer using a fiber optic or endoscopic laser [11].…”
Section: Gold Nanoparticles Block the Function Of Cancer Cellsmentioning
confidence: 99%
“…They also suspect they would be able to treat deeper cancer using a fiber optic or endoscopic laser [11].…”
Section: Gold Nanoparticles Block the Function Of Cancer Cellsmentioning
confidence: 99%